The influence of small doses of ethanol on the urinary testosterone to epitestosterone ratio in men and women. Issue 3 (1st August 2017) - Albeiroti, Sami; Ahrens, Brian D.; Sobolevskii, Timofei; Butch, Anthony W.
Abstract : Endogenous steroid use can increase urinary testosterone/epitestosterone (T/E) values. In addition, ethanol in amounts >0.5 g per kg of body weight (g/kg) can also increase T/E values. However, the effect of smaller doses of ethanol on T/E values is unknown. The influence of 0.2 and 0.4 g/kg of ethanol on baseline T/E values in 20 men and 20 women with low and high baseline T/E values was investigated and correlated with ethyl glucuronide (EtG) and ethyl sulfate (EtS) concentrations. T/E values for 7 of the women were excluded from the study because of undetectable T concentrations or for other reasons. One man and 1 woman with a high T/E baseline value had a significant increase in their T/E value after ingestion of 0.2 g/kg of ethanol. One man and 2 women with a high T/E baseline, and 1 woman with a low T/E baseline had significantly increased T/E values after ingestion of 0.4 g/kg of ethanol. There was wide variability in peak EtG concentrations and a lack of correlation between ethanol dose and EtG concentrations. Interestingly, 1 man and 2 women with increased T/E values following ethanol ingestion had EtG concentrations below the World Anti‐Doping Agency (WADA) cut‐off of 5000 ng/mL. These findings demonstrate that small amounts of ethanol can elevate T/E values, with women being more susceptible. In addition, consideration should be given to the lowering of the WADA EtG cut‐off to detect samples with elevated T/E values from ingestion of low doses of ethanol. Abstract : The effect of low doses of ethanol on urinary T/E values in men and women with low and high baseline T/E values was investigated. Ethanol at 0.2 and 0.4 g/kg of body weight produced elevated T/E values in 18% of the participants, with women being more susceptible to this effect. There was wide variation in peak ethyl glucuronide concentrations and 50% of the participants with elevated T/E values had ethyl glucuronide concentrations <5 μg/mL.